Contamination of yellow-feathered broiler carcasses: Microbial diversity and succession during processing. (October 2019) - Wang, Hang; Qin, Xiaojie; Mi, Si; Li, Xia; Wang, Xiaoling; Yan, Weijiang; Zhang, Chunhui
Abstract: The processing environment of broiler processing plants is a potential major source of bacterial contamination of broiler carcasses. This study investigated the effect of processing water and processing time on the microbial diversity of yellow-feathered broiler carcasses at select stages of slaughter during one commercial processing day using a high-throughput sequencing technique targeting the V3V4 region of the 16S RNA gene. Our results demonstrated that Firmicutes and Proteobacteria were the dominant bacterial phyla of broiler carcasses and processing water in the chiller tank, whereas the processing water in the scalder tank contained a high abundance of Firmicutes and Deinococcus-Thermus . At the genus level, Escherichia-Shigella and Streptococcus were present on broiler carcasses with high abundances after defeathering, but their abundance decreased after washing and chilling. The bacterial community structure was revealed to become more complex at later stages of processing, as indicated by the consistent increase in microbial alpha diversity metrics (Chao 1, Shannoneven and Shannon) throughout the processing stages ( p < 0.05). Significantly separate clustering of bacterial communities between scalder tank water and carcasses was revealed by PCoA analysis, indicating the limited effect of scalding water on the bacterial communities of broiler carcasses. Highlights: Firmicutes and Proteobacteria were the dominant phyla on broiler carcasses. Bacterial richness and diversity increased along with the processing stages. Escherichia-shigella and Streptococcus decreased after washing and chilling. Evisceration and chilling were identified as the main contamination points. Chilled carcasses shared higher OTUs with chiller water than scalder water.